Effect of Vacuum Packaging on the Shelf life of Fried Mussel, Pema viridis (Linnaeus) in Flexible Packaging Material - J., Bindhu; T.K., Srinivasa Gopal; A.C., Joseph; T.S.U., Nair; K., George Joseph (Fishery Technology, 2025)
A method for preservation of fried mussel, Pema viridis (Linnaeus) at ambient temperature was developed. Live mussels from rocky structures of the North Kerala waters were collected, and the meat shucked from them was used for preparation of samples. The cleaned meat was deep-fried in refined vegetable oil at 170-180oC for 6 minutes in an electric fryer. Roasted condiments were added to fried mussel meat and was packed under vacuum and in air in flexible pouches made of 12 |i plain polyester laminated with 118 (.1 LD-HD co-extruded films. The samples packed under vacuum had a storage life of 9 months and those packed in air were acceptable for a period of 6 months.